Advances in Information and Computer Security c - Aoki, Kazumaro; Kanaoka, Akira; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book constitutes the refereed proceedings of the 15th International Workshop on Security, IWSEC 2020, held in Fukui, Japan, in September 2020.* The 15 regular papers and 1 short paper presented in this volume were carefully reviewed and selected from 47 submissions. They were organized in topical sections named: symmetric-key cryptography, malicious activity detection, multiparty computation, post quantum cryptography, privacy, pairing-based cryptography, and machine learning. * The conference was held virtually due to the COVID-19 pandemic.
Symmetric-Key Cryptography 1 -- Malicious Activity Detection 1 -- Multiparty Computation -- Malicious Activity Detection 2 -- Post Quantum Cryptography -- Symmetric-Key Cryptography 2 -- Privacy -- Pairing-Based Cryptography -- Machine Learning.
Keywords: Computer security; Computer organization; Computers; Artificial intelligence; Software engineering; Systems and Data Security; Computer Systems Organization and Communication Networks; Information Systems and Communication Service; Computing Milieux; Artificial Intelligence; Software Engineering/Programming and Operating Systems